Molecular Docking Analysis of D-Glucosamine and Rivastigmine Tartrate Targeting Alzheimer’s Disease-Associated Proteins: An In Silico Approach - Jain, Sanjay K. (Asian Journal of Pharmaceutics (AJP), 2024)
Aims: The primary aim of this study is to investigate the potential interactions of D-glucosamine and rivastigmine tartrate with key receptors associated with Alzheimer’s disease (AD) using in silico docking analysis. By utilizing the Glide software, the study seeks to explore the binding affinities of these compounds with targets such as acetylcholinesterase (AChE), microglia, astrocytes, and the sigma-1 receptor, aiming to identify potential therapeutic implications. Objectives: The objectives of this study are to conduct a comprehensive molecular docking analysis of D-glucosamine and rivastigmine tartrate using the Glide software to evaluate their binding interactions with key Alzheimer’s disease (AD)-associated receptors. Specifically, the study aims to assess the binding affinities of these compounds with acetylcholinesterase (AChE), microglia, astrocytes, and the sigma-1 receptor. By comparing the docking scores, the research seeks to determine the relative binding strengths of D-glucosamine and rivastigmine tartrate with each target receptor. Additionally, the study aims to analyze the versatility and potential therapeutic relevance of these compounds in interacting with diverse AD-related receptors, providing insights into their potential roles in AD treatment. Conclusion: The in silico docking analysis revealed that rivastigmine tartrate exhibits stronger binding to the primary target enzyme AChE compared to D-glucosamine. Both compounds showed comparable binding potential for microglia. D-glucosamine demonstrated lower docking scores for astrocytes, while rivastigmine tartrate showed higher affinity for the sigma-1 receptor. These findings highlight the diverse interactions of D-glucosamine and rivastigmine tartrate with AD-associated receptors, suggesting the need for further in vitro and in vivo studies to validate these results and explore their potential therapeutic applications in Alzheimer’s disease treatment.